Endothelial function in response to exercise in the cold in patients with coronary artery disease. (20th April 2020) - Valtonen, Rasmus I. P.; Ikäheimo, Tiina M.; Hintsala, Heidi E.; Ryti, Niilo R. I.; Hautala, Arto; Perkiömäki, Juha S.; Crandall, C. G.; Mäntysaari, Matti; Jaakkola, Jouni J. K.; Kiviniemi, Antti M.
Abstract: Background: Regular long‐term physical exercise has favourable effects on endothelial function in patients with coronary artery disease (CAD). However, the effects of an acute exercise bout in the cold on endothelial function are not known. Methods: At first, the effects of moderate‐intensity aerobic lower‐body exercise were assessed in CAD patients ( n = 16) in a neutral [+22°C] and cold [−15°C] environment. Secondly, responses to static and dynamic upper‐body exercise in a neutral [+22°C] and cold [−15°C] environment were investigated in CAD patients ( n = 15). All experiments were performed in a random order. Endothelial function was measured by flow‐mediated dilation (FMD) of the brachial artery in response to reactive hyperaemia, before and after the exposures in a neutral environment. Results: No significant temperature*exercise*condition (pre–post) interaction was observed in FMD% when comparing rest versus aerobic exercise or static versus dynamic upper‐body exercise. Relative reactive hyperaemia during FMD protocol, measured by changes in shear rate, was elevated after rest compared to aerobic exercise ( p = .001) and after static compared to dynamic upper‐body exercise ( p < .001). However, no significant temperature*exercise*condition interaction was observed when FMD% was normalized for shear rate. Conclusions: Endothelial function to an acute bout of exercise among CAD patients was not modified by the environmental temperature where the exercise was performed. The present findings argue against the hypothesis that exercise in cold environmental conditions impairs endothelial function in patients with CAD.